2020
DOI: 10.1111/cts.12932
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adverse Events and Determinants of the Voriconazole Trough Concentration in Kidney Transplantation Recipients

Abstract: Voriconazole is the mainstay for the treatment of invasive fungal infections in patients who underwent a kidney transplant. Variant CYP2C19 alleles, hepatic function, and concomitant medications are directly involved in the metabolism of voriconazole. However, the drug is also associated with numerous adverse events. The purpose of this study was to identify predictors of adverse events using binary logistic regression and to measure its trough concentration using multiple linear modeling. We conducted a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
1
6
1
Order By: Relevance
“…Therefore, the interaction between tacrolimus and voriconazole has also been widely concerned [ 5 , 6 ]. The result of our previous study in kidney transplantation recipients was that the combination use of tacrolimus was associated with voriconazole concentration; however, in further multiple linear regression analysis, tacrolimus was not identified as the final influencing factor of voriconazole concentration [ 38 ], and the results were similar to those in this study. Taken together, the drugs mentioned above may have potential drug interactions with voriconazole, but the conclusions are inconsistent; it is also necessary to pay attention to the impact of drug combination during voriconazole therapy.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the interaction between tacrolimus and voriconazole has also been widely concerned [ 5 , 6 ]. The result of our previous study in kidney transplantation recipients was that the combination use of tacrolimus was associated with voriconazole concentration; however, in further multiple linear regression analysis, tacrolimus was not identified as the final influencing factor of voriconazole concentration [ 38 ], and the results were similar to those in this study. Taken together, the drugs mentioned above may have potential drug interactions with voriconazole, but the conclusions are inconsistent; it is also necessary to pay attention to the impact of drug combination during voriconazole therapy.…”
Section: Discussionsupporting
confidence: 83%
“…The result is similar to previous findings [19,38] and conforms to the metabolic characteristics of VRZ. It has been reported that ALP had a significant effect on VRZ concentration in kidney transplantation recipients [39] and oncology patients [30]. However, there was no similar result regarding ALP in the present study.…”
Section: Discussioncontrasting
confidence: 85%
“…The other research team members have drawn a similar conclusion for platelet count: platelet count was statistically significantly associated with voriconazole pharmacokinetics [ 35 ]. Except for the above factors, the variability of concentrations can be partly explained by non-linear kinetics, weight, liver function, concomitant medications [ 20 ], clinical and laboratory data such as C-reactive protein [ 17 , 36 ], albumin [ 37 ], and hemoglobin [ 38 ]. The different findings from these studies and the influence of sex found by this one may be due to the limited sample size and the large proportion of male patients (90.7%).…”
Section: Discussionmentioning
confidence: 99%